Engineering techniques to dendrite free Zinc-based rechargeable batteries - Worku, Ababay Ketema (Frontiers in Chemistry, 2022)
Rechargeable Zn-based batteries (RZBs) have garnered a lot of interest and are thought to be among the most promising options for next-generation energy storage due to their low price, high levels of safety, adequate energy density and environmental friendliness. However, dendrite formation during stripping/plating prevents zinc-based secondary batteries from being used in real-world applications. Dendrite formation is still a concern, despite the fact that inhibitory tactics have been put up recently to eliminate the harmful effects of zinc dendrites. Therefore, in order to direct the strategies for inhibiting zinc dendrite growth, it is vital to understand the formation mechanism of zinc dendrites. Therefore, for the practical application of zinc-based batteries, it is essential to use techniques that effectively prevent the creation and growth of zinc dendrites. The development and growth principles of zinc dendrites are first made clear in this review. The study and development of solutions to the zinc dendrite problem are then discussed, including strategies to prevent dendrite growth and subsequent creation as much as possible, reduce the negative impacts of dendrites, and create dendrite-free deposition processes. These methods' workings, benefits, disadvantages, and perspectives are shown. In order to fully address the issue of zinc dendrites, this overview of these techniques will improve comprehension of the creation process of zinc dendrites and give a professional, comprehensive, and extensive reference.